Pelatihan Basic Life Support Masyarakat Awam Di Masa Pandemi Covid-19 Tahun 2020 - siwi, ignasia (LPPM STIKES Madani, 2023)
Cardiac arrest is often discovered by ordinary people. The ability of ordinary people to act as first responders is an important key to the success of saving victims of cardiac arrest. Especially during the COVID-19 pandemic, first responders are really in need of assistance. The increased mortality rate due to COVID-19 is the reason basic life support training during the COVID-19 pandemic is urgently needed. This training aims to increase the knowledge and skills of participants. The training method was stimulation of Practice while Watching via online video with three materials: CPR for adults, CPR for babies, and Choking and Recovery Position skill stations, which were evaluated for each participant. The results of the training found the knowledge and skills of the participants after receiving training and simulation assistance when carrying out all the skills in this activity were better than before being given training.